Analysis of Tofu Product Quality Control Using Statistical Process Control (SPC) at UD Tata in Sidoarjo Regency - Ega Fadhilah Akbar; Rahmat Dhandy; Sekar Ayu Wulandari; Dini Nafisatul Mutmainah; Taufiq Rahman Humaidi (Fakultas Pertanian Universitas Almuslim Bireuen Aceh, 2026)
UD Tata is a tofu producer in Sidoarjo Regency that still faces quality deviations in the form of soft texture, visual damage, and product contamination. This study aimed to analyze tofu production quality control using Statistical Process Control (SPC). A quantitative approach with simple random sampling was applied to 1,000 tofu pieces per day for 20 observation days from a daily production of 10,000 pieces. The analysis employed check sheets, np control charts, Pareto diagrams, cause-and-effect diagrams, and process capability analysis. The results showed 596 soft-texture defects, 486 visually damaged tofu defects, and 443 contamination defects. The np control chart indicated that texture and visual attributes remained under statistical control, while the cleanliness attribute showed one point above the upper control limit on the ninth observation day and therefore required corrective action. The dominant defect was soft tofu texture, accounting for about 40% of total defects. The main causes were related to human factors, methods, materials, machines and equipment, and the work environment. Process capability values for the three attributes were categorized as good at 97.0%, 97.6%, and 98.0%, respectively.